Synthesis and Characterization of New Heterocyclic Compounds from 2, 5- dimercapto -1, 3, 4-Thiadiazole and Their Resins - Baghdad Science Journal (مجلة بغداد للعلوم)
In this research, a new 1, 3, 4-Thiadiazole derivatives have been synthesized by many heterocyclic reactions. Starting from (2, 5 – dimercapto -1, 3, 4-Thiadiazole) a variety of derivatives have been synthesis. Compound (1) was synthesized by the reaction of hydrazine hydrate with carbon disulphide in absolute ethanol. The compound (1) was reacted with 1, 2-dibromoethane in presence of alkali ethanol to give the compound (2). The compound (3) was formed from the reaction of compound (2) with hydrazine hydrate. Schiff base (4) was obtained by reacting of compound (3) with the compound (p-hydroxybenzaldehyde) in absolute ethanol. A variety of phenolic Schiff base (Methylolic, Etheric, and Epoxy) derivatives have been synthesized. Methylolic derivative was synthesized by the reaction of Schiff base (4) with formaldehyde in tetrahydrofuran (THF). Etheric derivative was formed from the reaction of a methylolic Schiff base (5) with saturated alcohol (Methanol).Epoxy derivative was synthesized by the reaction of epichlorohydrine with etheric derivative (6) .The last step of this research was the preparation of a composite material from mixing the Epoxy resin derivative(7), TiO2and morpholine via ring opening. All these derivatives were verified by using (FT-IR, UV) spectra photometer and 1H-NMR spectra. Also, these derivatives were characterized using elemental analysis (C.H.N.S) .